EDUCATION FOR PEACE AND HUMAN RIGHTS: THE CONTRIBUTION OF NON-VIOLENT COMMUNICATION (VERUM: Journal of Scientific Initiation, 2021)
This article reflects the need for peace education towards ensuring human rights, based on the theoretical-practical framework of Nonviolent Communication. It explores the perspective of a new culture called the culture of peace, within the antagonism between peace and violence, drawing from authors such as Galtung (2008), Jares (2007), Guimarães (2005), and Diskin (2008), important researchers in peace studies from the nonviolence perspective towards social pacification. This is the result of qualitative research, under the light of critical theory, produced from documentary and bibliographic research with already existing material. The present article proposes to review the concepts of Peace and Education. It provides guidance for an education where the foundation of relationships is based on human values, grounded in the practice of Nonviolent Communication.
Keywords: Education for Peace; Nonviolent Communication; Culture of Peace; Human Rights